PEROMBAKAN AIR LIMBAH TEKSTIL MENGGUNAKAN JAMUR PENDEGRADASI KAYU JENIS Polyporus sp TERAMOBIL PADA SERBUK GERGAJI KAYU - I D.K. Sastrawidana; Siti Maryam; I N. Sukarta (Environmental Research Center (PPLH) of Udayana University, 2012)
White-rot fungi produce ligninolytic enzymes including lignin peroxidase (LiP) and manganeseperoxidase (MnP). These enzymes can be applied to degrade azo textile dyes. The objective ofthis research was to study the potential of white-rot fungus which is identified as Polyporussp. for degrading textile wastewater. The Polyporus sp. was evaluated its ability to decolorizeazo dyes such as remazol black B and remazol red RB in solid media. Hereafter, the fungus wasimmobilized on sawdust and the results are used to reduce textile wastewater in an aerobicreactor system. The results revealed that the Polyporus sp. fungus immobilized on sawdust inan aerobic reactor system provides efficiency to decrease COD value up to 75,23%, BOD79,94%, TSS 53,18% and decolorization of textile dyes up to 73,48% within 7 days. Acutetoxicity test showed that moderate toxic textile categorized textile wastewater became lesstoxic.